DETERMINATION OF GYPSUM DIG ABILITY USING DRAG PICK - PITHALOKA (NIM : 12109007), DIAN
Mechanical excavation is now widely used in mining and civil engineering projects. The mechanical excavation equipment are equipped with cutting teeth. It is then important to analyse the forces acting on the cutting teeth.. This study aims to determine the magnitude of cutting force by using drag pick in the cut ability test on the blocks gypsum sample which has length, width and height each 60 cm x 20 cm x 25 cm with a depth variation of drag pick position from the upper surface of gypsum sample is 5 cm, 10 cm, 15 cm and 20 cm. Cutting force is obtained from the calculation of EvanÃ‚Â’s equation (1962), RoxboroughÃ‚Â’s equation (1973) and numerical calculation using Software Phase2. From the research can be concluded that the result of cutting force (Fc) obtained by using calculation of Evan's equation (1962), RoxboroughÃ‚Â’s equation (1973) and numerical model with Phase2 has a different magnitude. This is due to the differences in some parameters in each calculation methods such as cutting width (w) and rake angle (α).